Zonisamide, Topiramate, and Levetiracetam: Efficacy and Neuropsychological Effects in Alcohol Use Disorders - Knapp, Clifford M. (J Clin Psychopharmacol, 2015)
The anticonvulsant topiramate not only decreases ethanol consumption in alcohol dependence (AD) but also may produce several adverse events including cognitive impairment. Zonisamide is a structurally related anticonvulsant that is a promising agent for the treatment of AD and may have greater tolerability than topiramate. This study evaluated the effects of zonisamide (400 mg/d) on alcohol consumption and its neurotoxic effects in subjects with AD. A double-blind placebo-controlled clinical trial was conducted using 2 comparator anticonvulsant drugs, topiramate (300 mg/d) and levetiracetam (2000 mg/d), which does not impair cognition. Study medications were administered for 14 weeks, including a 2-week taper period. Medication adherence was facilitated using Brief Behavioral Compliance Enhancement Treatment. The neurotoxicity of the study drugs was assessed using neuropsychological tests and the AB-Neurotoxicity Scale. Compared with placebo, both zonisamide and topiramate produced significant reductions in the drinks consumed per day, percent days drinking, and percent days heavy drinking. Only the percent days heavy drinking was significantly decreased in the levetiracetam group. The topiramate cell was the only group that had a significant increase on the mental slowing subscale of the Neurotoxicity Scale compared with placebo at study weeks 11 and 12. Topiramate and zonisamide both produced modest reductions in verbal fluency and working memory. These findings indicate that zonisamide may have efficacy in the treatment of AD, with effect sizes similar to topiramate. Both of these drugs produced similar patterns of cognitive impairment, although only the topiramate group reported significant increases in mental slowing.